PROTACs: Walking through hematological malignancies - Bou Malhab, Lara J.; Alsafar, Habiba; Ibrahim, Saleh; Rahmani, Mohamed (Frontiers in Pharmacology, 2023)
Proteolysis targeting chimeras (PROTACs) are heterobifunctional small molecules that uses the proteasome ubiquitin system to target proteins of interest and promote their degradation with remarkable selectivity. Importantly, unlike conventional small molecule inhibitors, PROTACs have proven highly effective in targeting undruggable proteins and those bearing mutations. Because of these considerations, PROTACs have increasingly become an emerging technology for the development of novel targeted anticancer therapeutics. Interestingly, many PROTACs have demonstrated a great potency and specificity in degrading several oncogenic drivers. Many of these, following extensive preclinical evaluation, have reached advanced stages of clinical testing in various cancers including hematologic malignancies. In this review, we provide a comprehensive summary of the recent advances in the development of PROTACs as therapeutic strategies in diverse hematological malignancies. A particular attention has been given to clinically relevant PROTACs and those targeting oncogenic mutants that drive resistance to therapies. We also discus limitations, and various considerations to optimize the design for effective PROTACs.